KECERDASAN EKOLOGIS SISWA SEKOLAH DASAR MELALUI MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) PADA PEMBELAJARAN TEMATIK - Eliana Yunitha Seran; Ani Ani; Anna Marganingsih; Sirilus Sirhi (JURNAL PENDIDIKAN DASAR PERKHASA: Jurnal Penelitian Pendidikan Dasar, 2023)
Ecological intelligence is very important for elementary school students to have as a provision to be able to utilize nature for their survival today and in the future. Elementary school teachers play an important role in instilling ecological intelligence in students through the application of appropriate and contextual learning models. One of the appropriate learning models is the problem-based learning model. This study aims to (1) describe the application of the Problem Based Learning (PBL) learning model to increase students' ecological intelligence. (2) describe the improvement of students' ecological intelligence with the application of the Problem Based Learning (PBL) learning model in thematic learning. (3) describe students' responses to the application of the Problem Based Learning (PBL) learning model. This research uses a quantitative approach with a form of classroom action research (PTK). The subjects of this study were fifth grade students at SD Negeri Keberak, Belimbing Hulu District, Melawi Regency, totaling 23 people. The data collection tools used consisted of test questions, teacher observation sheets, student observation sheets, as well as teacher interview sheets and student interview sheets. The data analysis technique used was descriptive qualitative analysis and descriptive statistics. Descriptive statistical analysis is used to analyze quantitative data, while qualitative descriptive analysis is used to analyze qualitative data. The results of this study showed that: (1) cycle I student activity with an average of 66.5% (good category) and cycle II of 96.5% (very good category). (2) the percentage of classical completeness of ecological intelligence in cycle I was 73.91% (good category) the percentage of classical completeness in cycle II was 95.65% (very good category). The conclusion of this study is that the increase in ecological intelligence of students in thematic learning increases with the use of problem-based learning models.